2016
DOI: 10.1038/onc.2016.397
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic activation of the prostaglandin receptor EP4 promotes resistance to endocrine therapy for breast cancer

Abstract: Approximately 75% of breast cancers express estrogen receptor α (ERα) and depend on estrogen signals for continued growth. Aromatase inhibitors (AIs) prevent estrogen production and inhibit estrogen receptor signaling, resulting in decreased cancer recurrence and mortality. Advanced tumors treated with AIs almost always develop resistance to these drugs via the up-regulation of alternative growth signals. The mechanisms that drive this resistance—especially epigenetic events that alter gene expression—are howe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…More recently, EP4 has been implicated in treatment resistance and as a driver of CSCs. Epigenetic activation of the EP4 receptor may support resistance to endocrine therapy in patients with breast cancer that is reversed by GW627368x (Hiken et al, 2017). Several labs have shown that EP4 is upregulated in malignant cells with stem-like properties and that treatment of tumorbearing mice with EP4 antagonists (RQ15986, AH23848, Frondoside A) reduces the number of CSC (Kundu et al, 2014;Majumder et al, 2014).…”
Section: Cancer Stem Cells and Ep4 In Chemoresistancementioning
confidence: 99%
“…More recently, EP4 has been implicated in treatment resistance and as a driver of CSCs. Epigenetic activation of the EP4 receptor may support resistance to endocrine therapy in patients with breast cancer that is reversed by GW627368x (Hiken et al, 2017). Several labs have shown that EP4 is upregulated in malignant cells with stem-like properties and that treatment of tumorbearing mice with EP4 antagonists (RQ15986, AH23848, Frondoside A) reduces the number of CSC (Kundu et al, 2014;Majumder et al, 2014).…”
Section: Cancer Stem Cells and Ep4 In Chemoresistancementioning
confidence: 99%
“…Upregulation of the sphingosine 1-phosphate (S1P) 3 receptor in highly metastatic variants of a breast cancer cell line was shown to increase migration and invasion by the induction of PGE2 and EP2/EP4 activation [ 65 ]. Genome-wide DNA methylation and expression analysis of breast cancer cell line models of acquired estrogen resistance indicated that the EP4 receptor was upregulated by epigenetic mechanisms in demethylation resistant breast cancer cells [ 66 ]. In this study, EP4 was shown to be essential for estrogen-independent growth resulting from the activation of the ERα-cofactor CARM1.…”
Section: Cox2/pge2 Mediated Cancer Progressionmentioning
confidence: 99%
“…Gains are cancer-specific and normally include non-DNA-methylated CpG islands located in large regions of proximal promoters. These changes can be related to loss of gene expression, very similar to inactivating mutations on the abolition of tumor suppressor gene function through linked gene silencing; however, the activation of oncogenes also may occur 77 . In addition to DNA methylation, chromatin abnormalities are also observed in various types of tumors 78 .…”
Section: Genetic Heterogeneitymentioning
confidence: 99%